Unmasked - Jenkins, Jerry B.; LaHaye, Tim F.; Fabry, Chris (Wheaton, Illinois : Tyndale House Publishers, 2005)
"As another prophecy is fulfilled in Jerusalem, Judd and Lionel are startled by what they find. When they finally have the chance to head back to Illinois, they are thrown a detour and end up as witnesses to one of the most terrifying events of the tribulation. After running for their lives, the Young Trib Force find themselves looking for a new place to live in Wisconsin. Once in a new hiding place, Vicki and the others watch the frightening events in Israel while trying to tell others the truth."--Back cover.
Protected is a special edition compilation of the following Left behind : the kids titles: #26 : The beast arises ; #27 : Wildfire! ; #28 : The mark of the beast.
Keywords: Christian life -- Fiction; Fiction